Interface para controle e monitoramento de ambiente colaborativo em realidade virtual - Berwaldt, Natan Luiz Paetzhold (2023)
The growing interest in virtual reality (VR) devices has driven the generation of content for virtual environments (VEs). Part of this content is built upon the immersive experiences that VR can provide through real-time interaction, engagement, spatial perception, and enrichment of the overall experience. These aspects are beneficial for developing educational and training environments. However, using a virtual reality head-mounted display (HMD) disconnects users’ senses from the physical world they are currently in, and being immersed in the virtual environment makes it challenging for them to configure the simulation settings without breaking the immersion. With this in mind, this dissertation proposes developing a framework that combines multiple metaphors of indirect interaction into a unified virtual interface, enabling users to control collaborative simulations and effectively interact with other users within the virtual environment. The virtual interface is a reduced 3D representation of the environment, based on the World-in-Miniature metaphor, integrating state-of-the-art techniques with new features such as different ways of rendering, level of detail, and focus on specific regions of interest. We also present a technique for remote interaction using virtual cameras to enhance monitoring capabilities further, extending the Through-The-Lens technique with remotely controllable cameras and floating interaction panels that adapt to the user’s surroundings. The framework is finally evaluated in more detail when applied as a monitoring tool for instructors supervising a collaborative VR training simulation. We demonstrate how this system can facilitate various environment configurations and multiuser monitoring and interaction within the virtual environment without breaking the immersion.